Effect of Dietary Laminaria digitata with Carbohydrases on Broiler Production Performance and Meat Quality, Lipid Profile, and Mineral Composition - Costa, Mónica M. (2022)
We hypothesized that dietary inclusion of 15% Laminaria digitata, supplemented or not with carbohydrases, could improve the nutritional value of poultry meat without impairing animal growth performance. A total of 120 22-day old broilers were fed the following dietary treatments (n = 10) for 14 days: cereal-based diet (control); control diet with 15% L. digitata (LA); LA diet with 0.005% Rovabio® Excel AP (LAR); LA diet with 0.01% alginate lyase (LAE). Final body weight was lower and feed conversion ratio higher with LA diet than with the control. The ileal viscosity increased with LA and LAR diets relative to control but without differences between LAE and control. The pH of thigh meat was higher, and the redness value of breast was lower with LA diet than with control. Meat overall acceptability was positively scored for all treatments. The -tocopherol decreased, whereas total chlorophylls and carotenoids increased in meat with alga diets relative to control. The percentage of n-3 polyunsaturated fatty acids (PUFA) and accumulation of bromine and iodine in meat increased with alga diets compared with control. Feeding 15% of L. digitata to broilers impaired growth performance but enhanced meat quality by increasing antioxidant pigments, with beneficial effects on n-3 PUFA and iodine